Effect of EGFR-TKIs combined with craniocerebral radiotherapy on the prognosis of EGFR-mutant lung adenocarcinoma patients with brain metastasis: A propensity-score matched analysis - Deng, Guangchuan; Tan, Xiaojing; Li, Yankang; Zhang, Yingyun; Wang, Qi; Li, Jianbin; Li, Zhenxiang (Frontiers in Oncology, 2023)
Background and Purpose: Epidermal growth factor receptor (EGFR)-mutant lung cancers are associated with a high risk of developing brain metastases (BM). Craniocerebral radiotherapy is a cornerstone for the treatment of BM, and EGFR-TKI influences craniocerebral metastases. However, whether EGFR-TKIs combined with craniocerebral radiotherapy can further increase the efficacy and improve the prognosis of patients is unclear. This study aimed to evaluate the difference in efficacy between targeted-therapy alone and targeted-therapy combined with radiotherapy in EGFR-mutant lung adenocarcinoma patients with BM. Materials and Methods: A total of 291 patients with advanced non-small cell lung cancer (NSCLC) and EGFR mutations were enrolled in this retrospective cohort study. Propensity score matching (PSM) was conducted using a nearest-neighbor algorithm (1:1) to adjust for demographic and clinical covariates. Patients were divided into two groups: EGFR-TKIs alone and EGFR-TKIs combined with craniocerebral radiotherapy. Intracranial progression-free survival (iPFS) and overall survival (OS) were calculated. Kaplan–Meier analysis was used to compare iPFS and OS between the two groups. Brain radiotherapy included WBRT, local radiotherapy, and WBRT+Boost. Results: The median age at diagnosis was 54 years (range: 28–81 years). Most patients were female (55.9%) and non-smokers (75.5%). Fifty-one pairs of patients were matched using PSM. The median iPFS for EGFR-TKIs alone (n=37) and EGFR-TKIs+craniocerebral radiotherapy (n=24) was 8.9 and 14.7 months, respectively. The median OS for EGFR-TKIs alone (n=52) and EGFR-TKIs+craniocerebral radiotherapy (n=52) was 32.1 and 45.3 months, respectively. Conclusion: In EGFR-mutant lung adenocarcinoma patients with BM, targeted therapy combined with craniocerebral radiotherapy is an optimal treatment.